Interactions of factors in self-injuries among enrolled students: a network approach - Yu-Min Zhang; Xiao-Mei Jiang; Ya Xie; Nan Lang; Min-Lu Liang; Pei Zhang; Li-Chen OuYang; Zhang-Wei Lv; Cong-Wei Liu; Li-Ping Zhang; Chun Wang (Annals of General Psychiatry)
Abstract Purpose Suicidal and non-suicidal self-injuries are types of self-directed violence that can become complex health issues. This study assessed how and to what degree the factors of self-injuries are interrelated among enrolled students. Methods A total of 1481 students were recruited from college and middle or secondary schools, and 1465 (98.92%) subjects comprised the final sample. Mixed graphical models were used to establish network structures. Also explore their shortest paths and conduct a regression analysis. Results Of the 1465 students, we observed intersections that connected the cluster of early experiences and psychiatric/psychological using network analysis. Shortest paths analysis and regression analysis suggest that symptoms of schizoid (edge-weights = 0.336, OR = 2.79, p < 0.01) and narcissistic (edge-weights=-0.177, OR = 0.35, p < 0.05) personality disorders (PD), acceptance (edge-weights = 0.470, OR = 12.80, p < 0.01) and positive refocusing (edge-weights=-0.171, OR = 0.12, p < 0.05) strategies of emotion-regulation, mindfulness awareness (edge-weights=-0.263, OR = 0.24, p < 0.05), and emotional-neglect in childhood (edge-weights = 0.239, OR = 5.54, p < 0.05) were found with non-suicidal self-injury (NSSI). Symptoms of anxiety (edge-weights = 0.280, OR = 2.00, p < 0.01) and avoidant-PD (edge-weights = 0.229, OR = 1.75, p < 0.01) were associated with suicidal ideation, and symptoms of borderline-PD (edge-weights = 0.432, OR = 5.38, p < 0.05) and mindfulness awareness (edge-weights=-0.180, OR = 0.28, p < 0.05) were associated with suicide attempt. Conclusions Relying exclusively on acceptance strategy may constitute an avoidance pattern, impeding the ability to confront emotional distress. Clinical intervention aimed at repairing father-child relationship may be helpful to recover from emotional trauma and improve current symptoms and self-injuries.